A study of anthropometric differences among elite water polo players with different team role assignments - Pavicic, L.; Tomany, E.; Lozovina, V. (2001)
This study analyze differences in anthropometric status of elite water polo players, playing different team roles defined as; goalkeeper, guard, forward and centre. The sample of subjects consists of 66 water polo players from the population of the Croatian national league, aged from 19 to 29 years. Their anthropometric status defines 23 measures compromising lengths, girths, skinfolds, breadths and body weight. The analysis of variance showed statistically significant differences in the following measures: midstylion-dactilion length, foot breadth, femur breadth (p£ 0.001), body weight (p£ 0.005), calf girth, arm girth (relaxed), stature, and biliocristal breadth (p£ 0.05). The multivariate discriminative analysis showed that groups significantly differ along the two discriminative functions. Four girth measures and body weight define the first function and midstylion-dactilion length, biliocristal breadth, calf girth, arm length, body weight and stature define the second. A planar location of the group centroids shows that groups of centres and goalkeepers lay far apart in respect to the first function and have almost the same projections on the second function. The goalkeepers, compared to centres have notably smaller girths of chest and arm, smaller body weight and greater midstylion-dactilion length and stature. Forwards and guards groups compare very closely. In respect to the first function they are located approximately in the middle between the other two and their position in respect to the second function is away from other two groups in the direction of smaller values. It is concluded that centres tend to be endomezomorph, goalkeepers tend to be ektomesorph, and, forwards and guards groups tend to a balanced mezomorph somatotype.